EVALUASI PENERAPAN PERNYATAAN STANDAR AKUNTANSI PEMERINTAHAN (PSAP) NOMOR 05 TENTANG AKUNTANSI PERSEDIAAN PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN DAERAH PROVINSI SULAWESI UTARA - Ismail, Yulinar Mulyani; Karamoy, Herman; Pusung, Rudy J. (Universitas Sam Ratulangi, 2021)
Inventory is one of the current assets in the form of goods or equipment owned by a government agency to be used in supporting government administration activities and is intended to be sold and/or delivered as a service to the community. The purpose of this study was to determine whether the application of inventory accounting applied by the Regional Industry and Trade Office of North Sulawesi Province was in accordance with the Statement of Government Accounting Standards Number 05 (PSAP 05). This study uses a comparative qualitative descriptive method and research data obtained through interviews and documentation. The results showed that the inventory accounting at the Regional Industry and Trade Office of North Sulawesi Province was in accordance with PSAP No. 05. For Financial Reports and so on, the Regional Industry and Trade Office of North Sulawesi Province must always effective and the resulting financial reports can be presented appropriately to interested parties.